Analysis of VUS reporting, variant reinterpretation and recontact policies in clinical genomic sequencing consent forms. (December 2018) - Vears, Danya; Niemiec, Emilia; Howard, Heidi; Borry, Pascal
Abstract There are several key unsolved issues relating to the clinical use of next generation sequencing, such as: should laboratories report variants of uncertain significance (VUS) to clinicians and/or patients? Should they reinterpret VUS in response to growing knowledge in the field? And should patients be recontacted regarding such results? We systematically analyzed 58 consent forms in English used in the diagnostic context to investigate their policies for (a) reporting VUS, (b) reinterpreting variants, including who should initiate this, and (c) recontacting patients and the mechanisms for undertaking any recontact. One-third (20/58) of the forms did not mention VUS in any way. Of the 38 forms that mentioned VUS, only half provided some description of what a VUS is. Approximately one-third of forms explicitly stated that reinterpretation of variants for clinical purposes may occur. Less than half mentioned recontact for clinical purposes, with variation as to whether laboratories, patients, or clinicians should initiate this. We suggest that the variability in variant reporting, reinterpretation, and recontact policies and practices revealed by our analysis may lead to diffused responsibility, which could result in missed opportunities for patients or family members to receive a diagnosis in response to updated variant classifications. Finally, we provide some suggestions for ethically appropriate inclusion of policies for reporting VUS, reinterpretation, and recontact on consent forms.